Benign FGB (148Lys→Asn, and 448Arg→Lys), and novel causative γ211Tyr→His mutation distinguished by time of flight mass spectrometry in a family with hypofibrinogenaemia - Brennan, Stephen O.; Mangos, Hilda; Faed, James M. (Thrombosis and Haemostasis, 2014)
We describe a novel procedure for the direct analysis of plasma fibrinogen by HPLC time of flight (TOF) mass spectrometry and apply it to the investigation of a family with hypofibrinogenaemia. Electrospray TOF analysis provided much higher resolution than was possible with our previous quadrupole analyser and revealed three different mass changes within the fibrinogen Bβ and γ chains of the family. It also demonstrated the actual hypofibrinogenaemia phenotype was caused by an aberrant _ chain (-23 Da) which was expressed at a diminished ratio of 0.2:1 relative to γA and co-inherited with a second coequally expressed Bβ variant (BβM /BβA, 1:1). Co-segregation was confirmed by gene analysis that showed the affected father and son had a very rare Bβ148Lys→Arg mutation (-14 Da) inherited together with a unique new γ211Tyr→His mutation (-26 Da). This latter causative substitution occurs at a site that is absolutely conserved across all fibrinogen chains and preserved across all species. TOF analysis also identified a variant B_ chain (54,186 Da) that was coequally expressed with normal Bβ chains (54,213 Da) in the unaffected mother.
Keywords: Fibrinogen; fibrin; gene mutations; gene expression; inherited coagulation disorders; time of flight MS